2017
DOI: 10.1021/acs.molpharmaceut.7b00155
|View full text |Cite
|
Sign up to set email alerts
|

Design of HIV Coreceptor Derived Peptides That Inhibit Viral Entry at Submicromolar Concentrations

Abstract: HIV/AIDS continues to pose an enormous burden on global health. Current HIV therapeutics include inhibitors that target the enzymes HIV protease, reverse transcriptase, and integrase, along with viral entry inhibitors that block the initial steps of HIV infection by preventing membrane fusion or virus-coreceptor interactions. With regard to the latter, peptides derived from the HIV coreceptor CCR5 were previously shown to modestly inhibit entry of CCR5-tropic HIV strains, with a peptide containing residues 178… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…As was proved, this mutation has a protective role against chronic HBV infection and HIV, and also leads to a non-functional receptor that could modify disease in Rheumatoid arthritis patients, so it is concluded that the population of Birjand has greater hereditary susceptibility to chronic HBV infections, HIV, and Rheumatoid arthritis, compared to Europeans in terms of the CCR5 ∆32 mutation (13,14,18).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As was proved, this mutation has a protective role against chronic HBV infection and HIV, and also leads to a non-functional receptor that could modify disease in Rheumatoid arthritis patients, so it is concluded that the population of Birjand has greater hereditary susceptibility to chronic HBV infections, HIV, and Rheumatoid arthritis, compared to Europeans in terms of the CCR5 ∆32 mutation (13,14,18).…”
Section: Discussionmentioning
confidence: 97%
“…The CCR5 plays a role in T cell proliferation and activation by binding to its ligand RANTES (CCL5) and additionally works as the principal co-receptor for macrophage (M)-tropic strains of Human Immunodeficiency Virus type 1 (HIV-1) (14,15). The latest studies have demonstrated the protective role of homozygous for the CCR5 ∆32 genotype against HIV infection, yet in relation to heterozygous CCR5 ∆32 (∆32/wt), the results have been practically controversial (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…An example is peptide 2C which is derived from the C-terminal portion of the extracellular loop of CCR5. C2 competes with CCR5 for binding to gp120 [ 54 ] and inhibits HIV-1 entry at a double-digit micromolar concentration in vitro [ 52 , 18 ].…”
Section: Acquired Immunodeficiency Syndromementioning
confidence: 99%
“…As HIV entry process requires expression of both CCR5 and CD4 on cell membrane, receptor- and co-receptor-mimetic peptides ( 143 , 144 ) have been proposed as an alternative strategy to block HIV entry but, as for chemokines, no one has been already tested in human clinical trial.…”
Section: Other Strategies Aimed At Blocking Hiv Infection Through Ccrmentioning
confidence: 99%